Sustainable Distance E-Learning for Enhanced Students Retention and Support: Faculty of Law National Open University of Nigeria in Focus - Erimma Gloria Orie (West African Journal of Open and Flexible Learning)
The National Open University of Nigeria (NOUN) was primarily conceived to afford the teeming population of prospective university candidates the opportunity to access tertiary education in order to fulfill their life dreams, contribute to national socio-economic development in our ever competitive, contemporary and globalised world. The NOUN is ranked 7th in Nigeria, offers about 60 academic programmes including Law and has been delivering academic excellence in consonance with its mandate. The institution has 455,837 students as at April 2016 enrolled and has graduated 12000 students since re-launched in 2002 and in 2017 alone graduated 12000 students, the highest in any year since its relaunch in 2002. Despite the monumental progress made by NOUN, there are challenges related to students’ retention and support militating against realization of the objectives of establishing the university. These challenges stem from the peculiar nature of the Open University concept predicated on Distance Learning or e-Learning as means of service delivery. In a developing country like Nigeria, these challenges can be critical compared to the developed countries where infrastructural development is well in place and taken for granted. Therefore, there is need to combat the identified challenges particularly as they affect the Faculty of Law with its peculiarities and to proffer strategies to enhance students success on a sustainable basis at NOUN and thereby promote academic excellence. The paper is essentially predicated on relevant document analyses, interviews and discussions with students, interactions with fellow staff and facilitators who encounter students on a regular basis as well as personal experience as both a legal practitioner and lecturer in Law at NOUN. The motivation to examine the issues stem from the understanding that the pursuit of academic excellence vis-à-vis addressing the challenges inherent in e-Learning system for students’ retention and support could be conceived as a benchmark for evaluating students’ and institutional performances. Therefore, the paper explores the challenges related to students’ retention and support some of which are considered personal to the student; some are institutional while others are societal or external. Specifically, students’ background / orientation, state of infrastructure nationwide, funding and staffing inadequacies constitute the major issues. Strategies proffered to remedy the situation include pre-enrolment orientation in e-Learning environment and mentoring, improved budgetary allocation, improved ICT facilities including e-library, follow-up on students and proper staffing amongst others. Accordingly, recommendations were derived from the strategies to enhance students’ retention, support and ultimately success at the Faculty of Law NOUN.